Exposure assessment of the European adult population to deoxynivalenol - Namorado, Sónia (2024)
Funding Information: HBM4EU has received funding from the European Union\u2019s research and innovation programme Horizon 2020 under grant agreement No. 733032. The HBM4EU Aligned Studies were co-funded by the European Union\u2019s programme Horizon 2020 through HBM4EU and by the participating countries through the co-authors organizations. Publisher Copyright: © 2024 The Authors